Effects of corticosterone-induced depression in mouse default mode network - Kiiso, Tommi (My University, 2025)
Major depressive disorder (MDD) is a major cause of disability globally, with approximately 300 million people suffering from it worldwide. Current antidepressant treatments rely heavily on selective serotonin reuptake inhibitors, as well as selective noradrenaline reuptake inhibitors, and tricyclic antidepressants. However, these drugs are associated with long onset times, which can be preceded by serious adverse effects such as changes in weight, increased anxiety, and sexual dysfunction, and roughly 30 % don’t respond to current antidepressants properly. Additionally, the development of novel antidepressants has not achieved any major breakthroughs in several decades, meaning there remains a large unmet medical need in the treatment of depression. The default mode network (DMN) is one of the major resting-state networks, that has been characterised to have increased activity during internally oriented tasks, such as self-referential thinking, and decreased activity during externally oriented tasks, such as focused studying. The DMN has been previously shown to have altered activity in MDD patients, and it has been hypothesised that the increased activity of the DMN would be related to certain symptoms of MDD, like rumination and negative self-image. Therefore, researching the DMN’s functionality in healthy mice and mice with depression-like characteristics could provide new insights on its role in depression and possibly aid in the development of novel antidepressants. The aims of this thesis were to model the DMN in a depression-like state in mice to gain more knowledge of the DMN’s functional connectivity and activity in mice, and to study the oscillatory synchrony dynamics within the DMN to learn about its pathological characteristics in depression. By utilizing a novel electrophysiology setup consisting of two intracranial Neuropixels probes, and two cortical micro-electrocorticography grids, we recorded the activity of the DMN in healthy, control mice, and in mice that were administered corticosterone via drinking water for 21 days to model depression. In this study, we observed a decrease between the baseline and post-treatment synchrony in the posterior DMN regions and increase in the anterior DMN regions within the treatment group. Also, a dissociation between the front and back regions of the DMN was observed in the treatment group. With the functional connectivity, there was a clear decrease in the posterior sections and a more subtle increase in the anterior sections. Furthermore, no alterations in synchrony or connectivity were not observed in the control group to the same extent, suggesting a difference between the groups. In conclusion, depression-like state seems to alter the synchrony and functional connectivity of the DMN, possibly relating to symptoms of MDD, such as rumination and impaired memory control. However, due to a very small sample size and a topic with high variability in results, no clear conclusions could be made based on these results. Therefore, future studies need to confirm the results with larger cohorts, and comparison to equivalent human data acquired by EEG/MEG could provide translational value and more insights on the functionality of the mouse DMN.
Keywords: Depression, Default Mode Network, Electrophysiology, Neural plasticity